2018
DOI: 10.1111/cyt.12600
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycotic parotitis and otitis causing facial nerve palsy in a diabetic patient

Abstract: Mucormycosis of the parotid with facial nerve palsy is an uncommon manifestation of this fungal infection. Mucor is an angioinvasive and angiodestructive organism which can cause fatal infection in patients with altered immunity like Diabetes Mellitus and Hematological malignancies. It is essential to include it in the differential diagnosis to avoid delays in the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Facial nerve palsy occurs rarely with rhinocerebral mucormycosis 15 . It has also been reported previously in a single case of mucormycosis with parotiditis and otitis 3 . However, the exact pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Facial nerve palsy occurs rarely with rhinocerebral mucormycosis 15 . It has also been reported previously in a single case of mucormycosis with parotiditis and otitis 3 . However, the exact pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…The first case of parotid mucormycosis was reported in 1987 by MacDonell et al with only a few cases reported in the literature since then 1,3,7,12‐14 . Invasion into the parotid gland may occur from neighbouring sites such as the paranasal sinuses or from overlying cutaneous lesion 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In cases with isolated involvement of the parotid gland by mucormycosis leading to mucor parotitis, facial nerve palsy has been reported in the literature. 5,6 . https://doi.org/10.1017/S0022215121003510…”
Section: Discussionmentioning
confidence: 99%
“… 4 Facial nerve palsy has been reported in cases with isolated involvement of the parotid gland by mucormycosis, leading to Mucor parotitis. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%